Estrutura e propriedades de vidros niobatos - Araújo, Eudes Borges de (1995)
The family of lithium niobophophate glasses 0,5Li2O:(0,5-x)P2O5:xNb2O5:yFe2O3, with 0 ≤ x ≤ 0,5 (mol %) and y= 0,02 (mol %), were studied using Thermally Stimulated Depolarization and Polarization Current (TPDC/TSPC), X-ray powder diffraction, Infrared Spectroscopy and Mossbauer Spectroscopy. The use of these techniques gives new informations about the structure of niobium-phosphate glasses and glass-ceramics. The serie of glasses was prepared by melt quenching technique and studied with the aim to understand the function of the niobium ions in the physical properties of this system. LiNbO3crystals were detected for high niobium content samples, and also for x = 0,1 samples in special conditions. It was observed that under heat treatment the phosphorus-oxygen groups are formed in different degrees of complexity like LiPO3, Li4P2O7and Li3PO4.